Lakes - Hanson, Jeanne K.; Nash, Geoffrey H. (New York : Facts On File/Chelsea House, 2007)
Presents an introduction to lakes, describing how they originated and providing the history and current formation of ten of the world's most famous lakes.
Origin of the landform: Lakes -- Caspian Sea, Middle East -- Aral Sea, Western Asia -- Lake Superior, North America -- Lake Baikal, Central Asia -- Lake Titicaca, Western South America -- Lake Vanern, Northern Europe -- Lake Eyre, Australia -- Crater Lake, Oregon, United States -- Great Salt Lake, Utah, United States -- Great Slave Lake, Canada -- Conclusion: Lakes -- Glossary -- Books -- Web sites -- Magazines and journals -- Index.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Lakes; Electronic books; Electronic books